RELATIONSHIP OF PRIOR PULMONARY TUBERCULOSIS WITH THE OCCURRENCE OF COVID-19 PNEUMONIA: REVIEW OF 500 PLUS HRCT CHEST SCANS FROM TWO DIFFERENT CENTRES OF SINDH, PAKISTAN - Ahmed, Naveed; Hamid, Samar; Memon, Mubeen Ahmed (Journal of Ayub Medical College Abbottabad, 2021)
B Background: COVID-19 pandemic has severely affected the entire world. However, its severity and mortality rate are lesser in developing countries, including Pakistan. This study aims to determine the association of prior pulmonary tuberculosis with COVID-19 pneumonia. Methods: This cross-sectional study was conducted at two centres of Sindh, Pakistan. 521 HRCT chest performed from 1st May to 31st July 2020 were included and marked as COVID-19 group. 761 HRCT chest performed during the first six months of 2019 were retrospectively evaluated to determine the prevalence of prior pulmonary tuberculosis and marked as the pre-COVID-19 group. Previous pulmonary tuberculosis was documented as evidenced by clinical history, ATT intake and HRCT findings. Chi-square test was used to determine the association of prior pulmonary tuberculosis with COVID-19 pneumonia. A p-value of ‰¤0.01 was considered statistically significant. Results: In the COVID-19 group, 4.9% (n=26) patients had prior pulmonary tuberculosis. In the pre-COVID-19 group, 9.8% (n=75) patients had prior pulmonary tuberculosis with a confirmed history of tuberculosis in 8.9% (n=68) and without documented history in 0.9% (n=7) cases. A significant p-value of 0.001 was obtained with a confidence interval of 99%. Conclusion: Prior pulmonary tuberculosis might have a protective effect against COVID-19 pneumonia which could be due to developed antibodies secondary to exposure to prior tuberculosis or BCG vaccination. Our results warrant further consideration due to the potential public-health benefits that can be achieved in our fight against the novel pandemic.